E-leadership capacity and readiness for change in tackling learning innovation disruption in implementing Merdeka Belajar policy - Rusdinal, Rusdinal; Komariah, Aan; Budi Wiyono, Bambang; Meizatri, Ranti; Rifma, Rifma (Jurnal Cakrawala Pendidikan, 2024)
This study aims to analyze the e-leadership capacity of school principals and change readiness in dealing with the disruption of learning innovations to implement independent learning policies.This research was conducted using an ex post facto approach with a correlational study.The respondents were teachers (N=300) from 30 junior high schools in Sumatra Barat Province, Indonesia. The data were then analyzed using SEM Smart PLS. The analysis of the relationships between the variables was determined by referring to the original sample value and the T-statistic outputs from Smart PLS. The significant value of the path was determined using testing criteria with a significant value of (Î±) 5% and a T-statistic standard < 1.96. The results show that every relationship formed has a positive and significant relationship. It can be concluded that the e-leadership capacity variable has a positive and significant impact on readiness for change, learning innovation disruption, and Merdeka Belajar policy, as well as their indicators. This research recommends that school principals and school management teams increase e-leadership capacity so that the readiness of every element in the school to face changes is better. Thus, the disruption of learning innovation that continues to develop can be accommodated with good capacity from institutions and individuals. In this context, the Merdeka Belajar policy as an educational innovation in Indonesia can be implemented optimally.